Identificación de bacterias aisladas en ambientes hospitalarios de cinco clínicas veterinarias en la ciudad de Popayán - Cauca (2022)
Nosocomial transmission bacteria are a matter of great importance, since they are part of our daily lives, being responsible for multiple pathologies, these bacteria have no preference, because whatever the canine, feline or wild species, they will attack in the same way way. In the capital of the department of Cauca, it is the first proposed study where the types of bacteria in the facilities of veterinary clinics will be evaluated. The project is based on working with five veterinary clinics in which the busiest areas will be identified, such as the reception, office, surgery room, hospitalization and hands of the veterinary doctor on duty, once this is done, the samples are taken to happen to be cultivated in the different types of agars. As a final objective, what is sought is to recognize peculiar are the most common of the clinical bacteria evaluated and can better rethink the elimination protocols to achieve a significant reduction in the risk of contamination of patients by nosocomial transmission.